Gait capacity affects cortical activation patterns related to speed control in the elderly - Harada, Taeko; Miyai, Ichiro; Suzuki, Mitsuo; Kubota, Kisou (Experimental brain research, 2009)
Functional decline in locomotion is common among the elderly, and the prevalence of gait disorders increases with age. Recently, increasing interest has been focused on the influence of age-related decline in brain function and neurological disorders such as dementia and Alzheimer's disease on gait capacity. However, the neural mechanisms underlying gait control in the elderly remain poorly understood. We examined whether cortical activation patterns associated with the control of gait speed were related to the walking capacity in elderly subjects. Fifteen healthy elderly subjects participated in the study (mean ± SD 63 ± 4). Using functional near-infrared spectroscopy, we measured the changes in the cortical oxygenated hemoglobin (oxyHb) while the subjects walked on a treadmill at low, moderate, and high speeds corresponding to 30, 50, and 70% intensity of work load in each subject. We found a greater increase in oxyHb in the left prefrontal cortex (PFC) and the supplementary motor area (SMA) during walking at 70% intensity than at 50 or 30%. The degree of medial sensorimotor cortex (mSMC) and SMA activations was correlated with the locomotor speed and cadence. Heart rate response was only related with left PFC activation. Furthermore, at the highest speed, the change in the PFC activation was greater in subjects with low gait capacity than in those with high gait capacity. Our results indicate that the left PFC, SMA, and SMC control gait speed, and that the involvement of the left PFC might depend on an age-related decline in gait capacity in the elderly.